Human prehistory : exploring the past to understand the future - Barsky, Deborah, 1962- (New York : Cambridge University Press, 2022)
"More than 3 million years ago in Africa, our early ancestors began to systematically modify rocks into useable tools, thus inventing the first technologies that eventually permitted humans to dominate all life forms on the planet. In this book, Deborah Barsky offers a long-term evolutionary perspective on human culture and its relationship with technology. Using scientific information and examples from the global archaeological record, she follows the remarkable human journey from the early phases of prehistory and shows how it has led humans to a dangerously uncertain future. Her archaeological approach enables a fresh perspective regarding important issues that plague contemporary society, such as racism, the digital revolution, human migrations, terrorism, and war. Written in an accessible style, Barsky's book demonstrates how insights into the distant past serve as a tool for understanding the present and building a sustainable future for all life on planet Earth"--
Includes bibliographical references and index.
Keywords: Antiquities, Prehistoric; Prehistoric peoples; Archaeology